Your Country Needs You? Advertising, Public Relations and the Promotion of Military Service in Peacetime Britain. (June 2020) - Maartens, Brendan
Historians have long taken an interest in military recruitment advertising and public relations. Much of their attention, however, has been directed towards promotion in wartime, with a lot less known about how governments used media to attract civilians in peacetime or during the many so-called 'limited wars' of the post-war era. This article addresses this shortcoming by exploring three separate recruitment campaigns waged in Britain at different moments in the 20th century. Giving a sense of the scale of official recruiting work, it highlights the central role played by commercial advertising and public relations professionals in the planning and development of campaigns and investigates whether recruiters were actually successful in convincing civilians to join up. The evidence presented here suggests that they had a negligible effect on enrolment rates. Yet, it also indicates that different types of appeal were used to attract civilians in peacetime, with material rewards typically taking precedence over notions of patriotic duty. Suggesting that such appeals effectively commodified military service, this article concludes by reflecting on their broader legacy to studies of media, war and conflict.